# SOLVED EXAMPLES OF INTEGRATION

## About "Solved Examples of Integration"

Solved Examples of Integration :

Here we are going to see some example problems in integration.

## Solved Examples of Integration - Questions

Question 1 :

Integrate the following functions with respect to x :

ex log a ex

Solution :

∫[ex log a ex] dx

=  elog a^x ex dx

=  x ex dx

u = x, dv  =  ex

du  =  dx, v = ex

∫ udv  =  uv - ∫v du

x ex dx  =  x(ex) -  ex dx

=  xex - ex + c

=  x (ex -1) + c

Question 2 :

Integrate the following functions with respect to x :

(3x + 4)√(3x + 7)

Solution :

(3x + 4)√(3x + 7) dx

Let t = 3x + 7

3x  =  t - 7

3x + 4  =  t - 7 + 4  ==> t - 3

Differentiating with respect to "x", we get

dt  =  3 dx  ==> dx  =  dt/3

(3x + 4)√(3x + 7) dx  =  (t - 3)√t (dt/3)

=  (1/3)[∫ t√t dt - 3√t dt]

=  (1/3)[∫ t3/2 dt - 3t1/2 dt]

=  (1/3)[(2/5) t5/2 - 3 (2/3)t3/2]

=  (1/3)[(2/5) (3x + 7)5/2 - 2 (3x + 7)3/2] + c

Question 3 :

Integrate the following functions with respect to x :

(81 + x + 41- x) / 2x

Solution :

(81 + x + 41- x) / 2dx

=  (23(1+x) + 22(1-x) / 2dx

=  (23+3x + 22-2x) / 2dx

=  (23+3x-x  + 22-2x-x) dx

=  (23+2x  + 22-3xdx

=  (23+2x/2log 2)  - (22-3x/3 log 2) + c

=  (22+2x/log 2)  - (22-3x/3 log 2) + c

Question 4 :

Integrate the following functions with respect to x :

1/(√(x + 3) - √(x + 4))

Solution :

∫ 1/(√(x + 3) - √(x + 4)) dx

=  (1/(√(x + 3) - √(x + 4)) dx

Rationalizing the denominator, we get

=  ∫[(√(x + 3) + √(x + 4))/(x + 3) - (x + 4))]dx

=  -[∫(√(x + 3) + √(x + 4)) dx

=  - [∫(√(x + 3) dx + √(x + 4)) dx]

=  (2/3)(x + 3)3/2 + (2/3)(x + 4)3/2 + c

Question 5 :

Integrate the following functions with respect to x :

(x + 1)/(x + 2)(x + 3)

Solution :

∫ [(x + 1)/(x + 2)(x + 3)] dx

We have to use the concept partial fraction in order to integrate.

(x + 1)/(x + 2)(x + 3)  =  A/(x + 2) + B/(x + 3)

x + 1  =  A(x + 3) + B(x + 2)

Plug x = -2

-1  =  A  ===> A  =  -1

Plug x = -3

-2  =  -B  ===> B  =  2

(x+1)/(x+2)(x+3) dx =  -∫1/(x + 2) dx + ∫ 2/(x + 3) dx

= - log (x + 2) + 2 log (x + 3) + c

=  2 log (x + 3) - log (x + 2) + c

After having gone through the stuff given above, we hope that the students would have understood, "Solved Examples of Integration"

Apart from the stuff given in "Solved Examples of Integration", if you need any other stuff in math, please use our google custom search here.

Kindly mail your feedback to v4formath@gmail.com

## Recent Articles

1. ### SAT Math Videos

May 22, 24 06:32 AM

SAT Math Videos (Part 1 - No Calculator)

2. ### Simplifying Algebraic Expressions with Fractional Coefficients

May 17, 24 08:12 AM

Simplifying Algebraic Expressions with Fractional Coefficients

3. ### The Mean Value Theorem Worksheet

May 14, 24 08:53 AM

The Mean Value Theorem Worksheet